Evolution and Determinants of Non-Performing Loan Burden in The Group of Seven (G7) Banking Sector - Fitriani, F.; Yusuf, Muhammad; Maksar, Muhammad Sofian (Golden Ratio of Finance Management, 2025)
The banking sectors of G7 countries play a crucial role in supporting their economies, yet they remain fragile and susceptible to shocks that may threaten global financial stability. Non-performing loans (NPLs) represent a significant risk to the overall health of the banking system. This study investigates the factors that influence NPLs in the G7 banking sector during the period from 2019 to 2022. We assess the impact of both macroeconomic variables (economic growth, unemployment, and lending interest rates) and bank-specific variables (total assets, net interest income, Tier 1 capital ratio, and credit growth) on NPLs by employing a panel data regression model. The results indicate that economic growth and lending interest rates have a negative and statistically significant effect on NPLs, while the unemployment rate does not exhibit a significant impact. Among the bank-specific variables, only credit growth demonstrates a negative and significant relationship with NPLs. These findings offer valuable insights into the determinants of NPLs and can serve as a foundation for designing more effective risk mitigation strategies within the G7 banking sector.